Gerak Tubuh Wanita Sebagai Sumber Inspirasi Penciptaan Seni Lukis - Jati Putra, Komang Guntur; Karja, I Wayan; Utami, Ni Made Purnami (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
This independent study TA thesis raised the theme of women's body movements as a source of inspiration for the creation of painting, starting from an idea about the illustration of women's body movements which always have its own meaning in each of its beautiful forms. From this, it gives rise to the urge to present a visualization of female body movements by combining certain techniques and references to achieve the desired goals and meanings. The problem faced is how to visually process women's body movements to represent ideas so that the embodiment of the work looks attractive. The purpose and benefits are to provide a new reflection and elevate the existence of women's body movements which are full of use in various lessons for everyone. To answer what is the purpose of this work, the method of creation uses exploration, improvisation, and formation. By arranging elements of art, and going through the exploration, improvisation, and formation stages, as well as combining them with ideas and ideas, 6 works were created entitled: 1) "lonely", 2) "Doesn't care", 3) "Ballet dancers", 4) Fire dance”, 5) “tired”, 6) “Lie down” In the embodiment of the work, the author will use some technical references from other artists. By combining impressionist techniques and expressionist techniques using tile paint, acrylic in the visualization of beautiful works of art, and combined with the response of a brush that resembles cloth as in the catalog of painter Ida Bagus Indra to represent a movement, it is expected to produce quality works and become author's identity.